Study the Optical Properties of (PMMA-PS-TiO2) Nanocomposite - Mohammed, Musaab Khudhur; Hadi, Alaa Najah; abdulkadhim, Dalal Hassan; Rahid, Maher Hasan; Jassim, Khalid S (IJRDO-Journal of Applied Science, 2017)
In this paper, the effect of titanium oxide nanoparticles on optical properties for (PMMAPS) composite has been studied. The titanium oxide nanoparticles was added to the (PMMA-PS) composite for different weight percentages are (4, 8, 12) wt.%. The optical properties were measured in range of wavelength (200-1100) nm. The experimental results show that the absorbance of (PMMA-PS) composite was increased with the increase of titanium oxide concentrations. The optical constants and energy gap were changed with the addition of titanium oxide nanoparticles concentrations.